STUDI KASUS: ASUHAN KEBIDANAN PADA IBU HAMIL YANG MENGALAMI KETIDAKNYAMANAN SERING BUANG AIR KECIL - Hasnawati Nukuhaly; Kasmiati Kasmiati (Poltekkes Kemenkes Maluku, 2022)
Pregnancy is a vulnerable period for a mother, problems that will arise will cause problems in her pregnancy. Complaints that often occur in pregnant women can be in the form of discomfort which is often experienced in the third trimester, such as frequent urination which will cause problems such as urinary tract infections, yeast, itching, redness of the genital organs, and even premature labor. To prevent this from happening, conference care with a Continuity of Care approach to Mrs. M, GIVPIIIAO, 33 years old at CH. M. Tiahahu Ambon from June 20 to June 28 2021. Efforts are being made Conduct discomfort education, explain the physiology of the causes of frequent urination in the third trimester, maintain the cleanliness of the genital organs, and do Kegel exercises while still consuming 8 glasses of water a day, which can overcome the frequent urination experienced by Mrs.M. Health workers are expected to explain the physiology of the discomfort of urinating in pregnant women and do Kegel exercises during pregnancy so that mothers are able to prevent and overcome the discomfort of urinating.